Intelligent control of humanoid manipulation with uncertain weight objects. (5th May 2017) - Ahn, MinSung; Cho, SukHwan; Oh, ChaeYoun; Lee, SangRyong; Yi, Hak
This article addresses a new intelligent full-body balancing control framework on a full-sized humanoid robot for stably tracking a given reference while grasping onto objects with unknown weight information. Dealing with external uncertainty from the inherent stability of humanoid is an interesting challenge for developing stable manipulation performance during their operation. To this end, intelligent fuzzy-proportional–integral control scheme where parameters are adaptively adjusted to respond to those uncertainties is proposed in this study. Application of momentum information at the torso as additional information is to make the improvement of the manipulation capability on a humanoid over an unknown weight object. Results from both experiment and simulation over a range of unknown weight objects on humanoid hand verified that the proposed scheme is more representative of the intelligent control on humanoid operation with external uncertainties.